2018
DOI: 10.1515/iral-2015-0116
|View full text |Cite
|
Sign up to set email alerts
|

Korean L2 speakers’ regulatory focus and oral task performance

Abstract: The L2 motivation self system posits that motivation emerges from the dynamic interactions among a learner’s ideal L2 self, ought-to L2 self, and situated learning experience. Only a few studies to date have investigated the individual and combined impact of trait-based and task-induced motivation (i. e., situational motivation related to the immediate learning environment) on L2 performance. Therefore, the current study explored whether Korean L2 speakers’ trait-based and task-induced regulatory focus impacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 67 publications
(92 reference statements)
0
11
0
Order By: Relevance
“…In an SLA study, Papi (2018) showed that framing task instructions in promotion terms emphasizing gains rather than losses can induce a promotion induction and result in more task engagement and incidental vocabulary learning. Using promotion tasks requiring creativity and risk‐taking (Han & McDonough, 2018; Van Dijk & Kluger, 2004) could have similar effects and potentially reduce students’ L2 anxiety. These are only a few areas where promotion‐oriented teaching strategies could be employed to minimize L2 anxiety.…”
Section: Pedagogical Implicationsmentioning
confidence: 99%
“…In an SLA study, Papi (2018) showed that framing task instructions in promotion terms emphasizing gains rather than losses can induce a promotion induction and result in more task engagement and incidental vocabulary learning. Using promotion tasks requiring creativity and risk‐taking (Han & McDonough, 2018; Van Dijk & Kluger, 2004) could have similar effects and potentially reduce students’ L2 anxiety. These are only a few areas where promotion‐oriented teaching strategies could be employed to minimize L2 anxiety.…”
Section: Pedagogical Implicationsmentioning
confidence: 99%
“…Promotion induction can result in the use of eager strategic behaviors such as more participation, creativity, and risk taking; prevention priming can increase vigilant strategic behaviors such as attention to form, accuracy, and structure. In addition to its pedagogical utility, the perspective outlined in this article can provide a theoretical tool for L2 motivation researchers to move beyond descriptive studies of L2 motivation and toward employing rigorous motivational interventions to understand and promote cognitive and learning processes and outcomes, thereby creating a meaningful link between research on motivation and second language acquisition (Han & McDonough, 2017; see Papi, 2018).…”
mentioning
confidence: 99%
“…In another study, Han and McDonough (2021) found that a prevention focus harmed accuracy in L2 task performance, whereas a promotion focus had no effect on L2 task performance. Han and McDonough’s (2018, 2021) results do not precisely align with the findings of the previous studies in social psychology which were reviewed above probably because the researchers used the L2 specific measures of instrumentality-promotion and instrumentality-prevention (Taguchi et al, 2009) to measure dispositional regulatory focus, a practice whose validity has not been empirically established.…”
Section: Regulatory Focus Theorymentioning
confidence: 79%
“…In addition, prevention-focused learners learned more vocabulary items in a loss-framed condition than in a gain-framed condition. Han and McDonough (2018) found that learners’ general L2 regulatory focus did not influence their task performance but their task-induced prevention focus contributed to their speech fluency and accuracy more than their task-induced promotion focus. In another study, Han and McDonough (2021) found that a prevention focus harmed accuracy in L2 task performance, whereas a promotion focus had no effect on L2 task performance.…”
Section: Regulatory Focus Theorymentioning
confidence: 99%